Odpowiedzi

Najlepsza Odpowiedź!
2010-01-26T16:41:17+01:00
A). 3 - 3x + 2 = 7
-3x = 7 - 5
-3x = 2 | : (-3)
x = - 2/3
b). 12x + 8 - 2x + 8 = -2x + 13
12x - 2x +2x = 13 - 8 - 8
12x = -3 |:12
x = - 0.25
c). 4x - 8 - 2x - 8 = 5x - 3x
4x - 5x + 3x = 8+8
4x = 16 | :4
x = 4
2010-01-26T17:06:23+01:00
A)3(1-x)+2=-7
3-3x+2=-7
5-3x=-7 /-5
-3x=-12 /÷(-3)
x=4
b)4(3x+2)-2(x-4)=-(2x+13)
12x+8-2x+8=-2x-13
10x+16=-2x-13 /+2x
12x+16=-13 /-16
12x= -29 /÷12
x=-2 cale i 5/12
c)4(x-2)-2(x-4)=5(x=1)-3x
4x-8-2x+8=5x+5-3x
2x=2x+5 /-2x
0=5